Acquired immunodeficiency syndrome in a patient with no known risk factors: a pathological study. Issue 4 (April 1984) - Burt, A D; Scott, G; Shiach, C R; Isles, C G
Abstract : We present the pathological findings in a case of acquired immunodeficiency syndrome (AIDS) in a patient with no known risk factor. Postmortem examination showed klebsiella lung abscess, generalised cytomegalovirus infection, cerebral toxoplasmosis, and a primary cerebral lymphoma. An additional feature was the presence of dilatation of the intrahepatic large bile ducts in association with an atypical distribution of cytomegalovirus. The relation between this case and previously reported cases of AIDS is discussed.